DAMPE silicon tracker on-board data compression algorithm - 董亦凡 张飞 乔锐 彭文溪 樊瑞睿 龚轲 吴帝 王焕玉 (Chinese physics C, 2015)
The Dark Matter Particle Explorer（DAMPE） is an upcoming scientific satellite mission for high energy gamma-ray, electron and cosmic ray detection. The silicon tracker（STK） is a subdetector of the DAMPE payload.It has excellent position resolution（readout pitch of 242 μm）, and measures the incident direction of particles as well as charge. The STK consists of 12 layers of Silicon Micro-strip Detector（SMD）, equivalent to a total silicon area of6.5 m2. The total number of readout channels of the STK is 73728, which leads to a huge amount of raw data to be processed. In this paper, we focus on the on-board data compression algorithm and procedure in the STK, and show the results of initial verification by cosmic-ray measurements.